Kepemimpinan Agile di Sektor Publik: Tinjauan Sistematis Berbasis Transformational leadership - Gafur, Abdul (Universitas Muhammadiyah Makassar, 2025)
The transformation of public bureaucracy has become increasingly urgent amidst digital disruption and global complexity that demand rapid adaptation. This study aims to analyze the relationship between Transformational leadership and Agile leadership in supporting public sector reform, particularly in Indonesia. Using a Systematic Literature Review (SLR) approach, this article reviews 24 selected scholarly publications obtained through Google Scholar via Publish or Perish (PoP), covering the period from 2005 to 2025. The findings indicate that Transformational leadership significantly influences organizational culture, civil servant performance, and the quality of public services. Meanwhile, Agile leadership offers an alternative leadership style that is more adaptive in responding to uncertainty and policy dynamics. The integration of both approaches has the potential to create a public bureaucracy that is not only visionary and value-driven but also responsive, collaborative, and innovative. This review recommends the development of public leadership training that combines transformative values with organizational agility principles as a strategy to strengthen the national bureaucratic reform agenda.